Sistem Informasi Tracer Study Alumni Sekolah Menengah Kejuruan (SMK) Mandiri - Wardatul Jannah (ADA Journal of Information System Research, 2025)
Every year the number of alumni from schools is increasing, especially at the secondary school level. To identify alumni from a school, a track record of the alumni is needed. However, there are still many schools that do not have a track record of their alumni so that many schools still do not know what their alumni do after graduating from school. Meanwhile, data and information related to alumni are very useful for schools for various purposes, one of which is for the process of improving school accreditation. One of them is the Mandiri Vocational High School (SMK). Therefore, a system is needed that can answer the school's need for information on its alumni. So a system called the alumni tracer study information system was created. The information system was made web-based using the Laravel framework and uses a MySQL database and modeling using the Unified Modeling Language (UML). The results of the creation of the alumni tracer study information system will greatly assist schools in the process of collecting data about alumni both in terms of time, accuracy and good results. This system can help in overcoming obstacles and barriers that exist at Mandiri SMK, especially those related to the alumni data collection process. This system will also facilitate the process of searching for alumni data and information when needed by the school.